Investigating athletes` retirement from sport: From decision-making to optimal support programmes - Park, S. (2012)
This thesis aimed to extend knowledge of athletes. career transitions through examining athletes. retirement decision-making process and influence of cultural diversity and organisational culture on the process of career transition. The purpose of Study 1 was to identify the current status of knowledge in the study area through providing a systematic review of the athlete career transition studies. The findings provided up to date knowledge in the study area and suggested potential future research directions. Study 2 aimed to understand Korean tennis players career transition out of sport experiences via longitudinal qualitative research. The results indicated that athletes perceived making the retirement decision was difficult process for them and revealed that participants. experiences were influenced by cultural aspects and sport contexts of Korea. Study 3 focused on exploring the athletes. retirement decisionmaking process among Korean tennis players. Results showed that athletes. leaving from sport decision-making is a complex and multidimensional process, and the transtheoretical model was helpful in explaining athletes. retirement from sport decision-making. The objective of Study 4 was to explore the processes involved in the development of an athletes. career transition programme. Results revealed that the organisation might have influence on athletes. retirement decision and the quality of career transition. Overall, the findings from the current thesis provide advanced useful knowledge on the athlete career transition process, and such knowledge may assist attempts to enhance athletes. well-being and welfare for during and post-sport life.